2019
DOI: 10.1088/1755-1315/348/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of income level of skipper fishermen in Belawan Bahari Village, Medan Belawan District

Abstract: The Indonesian economy has experienced fairly good growth in recent years, especially in the fisheries and marine sector. The province of North Sumatra is one of the regions with a potential economic structure in fisheries considering the average number of fish produced in the region monthly. The puIDRose of this study therefore was to determine the income level of skipper fishermen in Belawan Bahari Village, Medan Belawan District. The study population furthermore was made up of skipper fishermen and the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Other problems that can be seen are the large number of ship activities at the Belawan OFP, which throw waste from fishing into the port pool, the waters contain heavy metals, the condition of the availability of WWTP facilities, the port environment is muddy and dirty due to trading activities (fish hatch ice liquid and fish pieces), aspects other environments that reduce environmental quality due to activities at the Belawan OFP, and biota such as shellfish and fish containing lead and heavy metals. This condition aligns with the research results of Lubis et al, (2015), who found that heavy metal lead pollution levels in stonehead fish and Sembilang fish have exceeded the maximum threshold.…”
Section: Introductionsupporting
confidence: 91%
“…Other problems that can be seen are the large number of ship activities at the Belawan OFP, which throw waste from fishing into the port pool, the waters contain heavy metals, the condition of the availability of WWTP facilities, the port environment is muddy and dirty due to trading activities (fish hatch ice liquid and fish pieces), aspects other environments that reduce environmental quality due to activities at the Belawan OFP, and biota such as shellfish and fish containing lead and heavy metals. This condition aligns with the research results of Lubis et al, (2015), who found that heavy metal lead pollution levels in stonehead fish and Sembilang fish have exceeded the maximum threshold.…”
Section: Introductionsupporting
confidence: 91%
“…Hal ini perlu direspon oleh pemerintah daerah dengan menggali potensi-potensi daerah yang mampu mendongkrak pertumbuhan ekonomi. Perlu adanya peningkatan kemampuan penduduk di daerah dalam memanfaatkan peluang ekonomi daerah (Ngatini et al, 2020;Lubis et al, 2019). Akademisi dan pemerintah dapat berkolaborasi meningkatkan pengetahuan dan keterampilan langsung kepada penduduk berbasis kearifan lokal (Julianti et al, 2018;Syahza, 2019).…”
Section: Uji R 2 (Koefisien Determinasi)unclassified